(untitled) (International Journal of Food and Nutritional Sciences, 2022)
History displays how women are dominated for ages to ages. The patriarchal society is not ready to give what they crave for. In Indian Literature, during the period of pre – Independence, many women writers are emerged and explore the female characters in the male